High quality atomically thin PtSe2 films grown by molecular beam epitaxy. (14th September 2017) - Yan, Mingzhe; Wang, Eryin; Zhou, Xue; Zhang, Guangqi; Zhang, Hongyun; Zhang, Kenan; Yao, Wei; Lu, Nianpeng; Yang, Shuzhen; Wu, Shilong; Yoshikawa, Tomoki; Miyamoto, Koji; et al.
Abstract: Atomically thin PtSe2 films have attracted extensive research interests for potential applications in high-speed electronics, spintronics and photodetectors. Obtaining high quality thin films with large size and controlled thickness is critical. Here we report the first successful epitaxial growth of high quality PtSe2 films by molecular beam epitaxy. Atomically thin films from 1 ML to 22 ML have been grown and characterized by low-energy electron diffraction, Raman spectroscopy and x-ray photoemission spectroscopy. Moreover, a systematic thickness dependent study of the electronic structure is revealed by angle-resolved photoemission spectroscopy (ARPES), and helical spin texture is revealed by spin-ARPES. Our work provides new opportunities for growing large size single crystalline films to investigate the physical properties and potential applications of PtSe2 .